1996
DOI: 10.1116/1.588561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface cleaning on electrical properties for Ni contacts to p-type ZnSe

Abstract: Articles you may be interested inElectrical and microstructure analysis of ohmic contacts to p-and n-type GaSb, grown by molecular beam epitaxy J.As a first step to achieve our goal to prepare Ohmic contacts to p-type ZnSe using a conventional deposition and annealing method, the microstructure and chemical composition of the ZnSe surface were analyzed by x-ray photoelectron spectroscopy, reflection high-energy electron diffraction, and reflection electron microscopy. A thin native oxide layer consisting of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This can be achieved either by performing surface preparation to reduce the metal-semiconductor barrier height which would allow to increase carrier tunneling probability or by increasing the effective carrier concentration of the surface perhaps taking advantage of oxygen loss. [552][553][554][555] Ohmic-contact metallization should be one of the main goals in improving device performance which plays an important role in device technology. 553 Although a lowresistance Ohmic contact on wide-band-gap semiconductors can be obtained by thermal annealing, surface roughness and structural degradation of the interface can be induced during the thermal annealing process, 556,557 resulting in poor device performance and reliability.…”
Section: A Ohmic Contacts To Znomentioning
confidence: 99%
“…This can be achieved either by performing surface preparation to reduce the metal-semiconductor barrier height which would allow to increase carrier tunneling probability or by increasing the effective carrier concentration of the surface perhaps taking advantage of oxygen loss. [552][553][554][555] Ohmic-contact metallization should be one of the main goals in improving device performance which plays an important role in device technology. 553 Although a lowresistance Ohmic contact on wide-band-gap semiconductors can be obtained by thermal annealing, surface roughness and structural degradation of the interface can be induced during the thermal annealing process, 556,557 resulting in poor device performance and reliability.…”
Section: A Ohmic Contacts To Znomentioning
confidence: 99%
“…3. Current density-voltage (J-V) characteristics of Ni contact to p-ZnSe [7]. ing to our measurement [14,15].…”
Section: Ohmic Contact Materials For P-type Ganmentioning
confidence: 99%
“…It can be seen that the current injection from the Ni contact is drastically increased by cleaning the p-ZnSe surface with SBW solution. From the analysis by X-ray photoelectron spectroscopy, this has been attributed to the removal of native oxide such as SeO x or ZnO [7]. It is concluded that the surface cleaning process is important for the formation of DA contact material.…”
Section: Ohmic Contact Materials For P-type Znsementioning
confidence: 99%
“…Among group III elements, Ga is one of the most effective donor dopants for ZnO due to its low electronegativity and ion radius similar to Zn, which allow substitution on Zn lattice sites without causing significant lattice distortion. 22 Moreover, the approaches to form Ohmic contacts can be intentionally doped using impurities, 23,24 or surface cleaning techniques 25 to modify the surface and reduce barrier height, and related transport over the contact has been investigated thoroughly. 26 In this study, we showed a novel nanocontacting scheme of low-resistance Ohmic contacts on ZnO nanowires without further heat treatment.…”
Section: Introductionmentioning
confidence: 99%